Screening results correlating to personality disorder traits in a new employee population of People's Republic of China - Tan Y; Liu Y; Wu L (Neuropsychiatric Disease and Treatment, 2016)
Yan Tan,1,* Yan Liu,2,* Lei Wu3 1Editorial Department, Academic Journal of Chinese People’s Liberation Army Medical School, Chinese People’s Liberation Army General Hospital, 2Department of Clinical Psychology, Beijing Huilongguan Hospital, 3Department of Epidemiology, Institute of Geriatrics, Chinese People’s Liberation Army General Hospital, Beijing, People’s Republic of China *These authors contributed equally to this work Background: Adaptation to a new environment may have an uncertain influence on young employees, whose values are still being formed during early adulthood. To understand the current mental status and further improve the mental health level of the new employee population of People’s Republic of China, we conducted a cross-sectional study to screen the prevalence and correlates of personality disorder (PD) traits in this population.Methods: This study included all male participants who were new employees (those who had started working in approximately the last three months) from 12 machinery factories in People’s Republic of China. The Personality Diagnostic Questionnaire-4+ was used to evaluate the mental status of all participants. The Connor–Davidson Resilience Scale was used to assess the resilience of the study participants.Results: A total of 3,960 male participants were included in the analysis. The mean age of the study participants was 18.7±1.5 years. The mean values of all PD subtypes were scored from 0.74 to 2.90, with a total of 16.85. Of all 10 PD traits, obsessive–compulsive, histrionic, and narcissistic scored the highest. PD traits scored significantly higher among participants who had higher education levels, came from a single-parent (divorced or separated) family, were raised in a neglectful parental rearing pattern, were the only child of the family, were living in city areas, or had a lower family income. All subtype PD traits were significantly and negatively correlated with resilience.Conclusion: Education level, single-parent family, parental rearing pattern, only-child status, living place, and family income may influence the development of PD traits. Additional high-quality studies are needed to learn more about the mental health status of new employees. Optimal interventions are warranted to avoid potential adverse events in this population. Keywords: personality disorder, risk factor, Chinese employee, new workers, resilience